The Average Age of Menopause and Its Associated Factors Among Women in Tehran - F. Jafari; N. Zafarghandi; M. Abbasi; Z. Khodashenas (Bihdād, 2013)
Background: Menopause means the permanent cessation of menstruation and lead to the fixed and permanent changes in women and is predisposing factors of chronic diseases. So the investigating of average age of menopause and some predictive factors are very important that this study was designed with this goal. Methods: This study was a cross sectional study with descriptive and analytical aspects that was done on the 403 women residing in 1 to 4 regions of Tehran and they had at least 1 year of the last menstruation and their menopause had occurred naturally. Data collection tool was a researcher made questionnaire. Then data were analyzed with SPSS software and Chi square, t-test, analysis of variance and correlations. Results: The mean age of subjects was 51.30±4.8 years. 89.4 percent were married and the average number of children was 2.61±1.07 and mean body mass index was 26.19±3.66. The average age at first menarche was 13.59±1.58 years. The average age at menopause in the understudy population was 46.57±4.95 years. Also, association between menopause and underlying demographic variables including age at menarche, education, height, weight, BMI, number of children, abortion, history of hormone use were examined in this study. Conclusion: With regard to life expectancy, women spend approximately one third of their life after menopause. Identification of factors associated with these issue particularly aspects of quality of life is important.